PEMETAAN POTENSI KOMODITAS PANGAN DI PULAU JAWA - Andhatu Achsa; Rian Destiningsih; Dian Marlina Verawati; Dinar Melani Hutajulu (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
The focus of this research is mapping the pattern and structure of provincial economic growth in Java with the Klassen typology approach, the potential of provincial food commodities in Java with the Static location quotient (SLQ)- Dynamic location quotient (DLQ) approach, and identifying the level of accessibility of provinces in Java with the Connectivity quotient CQ approach. Food commodities in this case include rice, corn, soybeans, peanuts, green beans, cassava, sweet potatoes. The results show that (1) DKI Jakarta occupies the position of quadrant I; (2) potential rice , corn and mung bean commodity in Central Java Province, , soybean commodity in East Java Province, peanut commodity in DIY, cassava commodity in West Java Province, as well as potential sweet potato commodities in the Provinces of Central Java and East Java; (3) furthermore, the high level of accessibility in four provinces in Java Island and the rest, namely Banten and East Java Provinces are classified as low accessibility levels.